2017
DOI: 10.2147/ijn.s143927
|View full text |Cite
|
Sign up to set email alerts
|

Poly(2-(diethylamino)ethyl methacrylate)-based, pH-responsive, copolymeric mixed micelles for targeting anticancer drug control release

Abstract: We have demonstrated a novel drug delivery system to improve the selectivity of the current chemotherapy by pH-responsive, polymeric micelle carriers. The micelle carriers were prepared by the self-assembly of copolymers containing the polybasic poly(2-(diethylamino) ethyl methacrylate) (PDEAEMA) block. The mixed copolymers exhibited a comparatively low critical micelle concentration (CMC; 1.95–5.25 mg/L). The resultant mixed micelles were found to be <100 nm and were used to encapsulate the anticancer drug do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 43 publications
(49 reference statements)
0
15
0
Order By: Relevance
“…Besides, it becomes clear that acidic media promoted the increase of the rates of PZQ release, confirming once more the formation of pH‐sensitive copolymers. As explained early, the protonation of the amine groups at acidic media lead to hydrophilic structures, promoting the swelling of the particles and therefore the more efficient release of the drug . On the other hand, in basic media it becomes possible to observe the slower release kinetics, ratifying the pH‐sensitive response of the produced copolymers.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Besides, it becomes clear that acidic media promoted the increase of the rates of PZQ release, confirming once more the formation of pH‐sensitive copolymers. As explained early, the protonation of the amine groups at acidic media lead to hydrophilic structures, promoting the swelling of the particles and therefore the more efficient release of the drug . On the other hand, in basic media it becomes possible to observe the slower release kinetics, ratifying the pH‐sensitive response of the produced copolymers.…”
Section: Resultsmentioning
confidence: 95%
“…Another approach used to confirm the incorporation of the comonomers into the polymer chains was the evaluation of contact angle analyses in acidic media. It is believed that the diethylaminoethyl and dimethylaminoethyl groups present in PDEAEMA and PDMAEMA, respectively, can be protonated, resulting in more hydrophilic structures . It is known that the increase of the hydrophilicity of the material leads to reduction of the contact angle between the material and the aqueous phase .…”
Section: Resultsmentioning
confidence: 99%
“…Traces of symmetric GPC distribution showed the uniformity of the copolymers via free radical polymerization. [ 30 ]. These unimodal curves showed that the polymerization was completed successfully and that there was no unreacted monomers in the reaction product.…”
Section: Resultsmentioning
confidence: 99%
“…Samples were washed carefully with phosphate buffer solution (PBS) (1/100 mL) to remove unattached cells and subjected them to SEM fixation. 100–200 µL of 4% para formaldehyde (PFA) was placed on washed samples and allowed to dry for 30–40 min [ 30 , 31 ]. Samples were washed with 25%, 50%, 70% and 100% concentrations of ethanol.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…SEM micrographs shown in Figure 17 show that the copolymer microparticles were spherical but exhibited rough and irregular surfaces, with the formation of some agglomerates. This is certainly due to the higher hydrophilicity of the cationic copolymers, which are partially soluble in water and tend to accumulate on the particle surfaces.…”
Section: Resultsmentioning
confidence: 99%